¿Quién consumiría el arbitraje de consumo?: el problemático caso a favor del acceso a la justicia de consumo - Rodríguez García, Gustavo M. (2017)
Consumer arbitration seeks to resolve, on a voluntary, fast and legally binding way, conflicts between consumers and suppliers. Consequently, the consumers obtain a definitive solution to the problems arisen with companies in a much shorter term and even receiving compensation for damages. However, what happens when access to this procedure is no longer universal for all consumers?.In this article, the author reveals the problems surrounding access to consumer justice and to discover whether national mechanisms, as designed, actually achieve their protection objectives.